Charting Science: Fuat Sezgin's Contribution to Science History Writing in the Islamic World (1250-1800) - Ansori, Fahmi Moh; Jufri, Muhammad Arman Al; Hidayat, Muhammad; Maknunah, Anun Bidl (Universitas Islam Negeri Raden Intan Lampung, 2024)
Writing the history of science in the Islamic world has become a study among Orientalists and Muslim scholars themselves. One of the scientists who focused on the study was Fuat Sezgin. His work in the field of history of science was a major influence on the recognition by Orientalists of the splendor of science in the Islamic world. Fuat Sezgin is popular among researchers in Indonesia for his critical studies of hadith, but pays little attention to the study of the history of science. He has major works that have influenced the development of writing the history of science among Eastern and Western scholars, especially Orientalists. This article uses an intellectual biography writing model, using a historical approach, using heuristics, verification, interpretation and historiography steps. This article adds to the scientific treasures in order to introduce Fuat Sezgin and his contribution to writing the history of science in the Islamic world. Fuat Ssezgin's contribution to writing the history of science in the Islamic world is recognized by eastern and western scholars. First, he was a continuation and complement to the studies of the history of science by Orientalists such as Carl Brocklemann and Helmut Ritter. Secondly, Fuat Sezgin presents authoritative primary sources that can be used as material for philological studies of Islamic science manuscripts. Third, he is not only limited to theory in the realm of research. However, he established a museum and institution that focused on the study of Islamic science.